Perancangan Sistem Informasi Akuntansi pada CV. KA - Sudrajat, Ari; Anwar, Sifaul (Jurnal Bangkit Indonesia, 2024)
Processing accounting data on CV. KA still has problems, because recording the same data in several books can result in writing errors due to employee boredom and physical fatigue. The process of publishing reports still involves copying data and calculations which can also produce inaccurate information. This certainly has a negative impact on the company if the reports used as decision-making material still contain incorrect information. To overcome this obstacle, the researcher proposes creating an accounting application system according to the accounting flow that applies to CV. KA. In the initial stage, the researcher proposed a design for an accounting information system that would be implemented in the form of entity relationship diagrams, data flow diagrams, and use case diagrams, starting with posting the ledger, compiling a work sheet, compiling a balance sheet, compiling profit and loss calculations, and compiling a balance sheet. closing balance.